A TRPV family ion channel required for hearing in Drosophila. - Kim, J.; Chung, Y.D.; Park, D.Y.; Choi, S.; Shin, D.W.; Soh, H.; Lee, H.W.; Son, W.; Yim, J.; Park, C.S.; Kernan, M.J.; Kim, C. (Nature, 2003)
The many types of insect ear share a common sensory element, the chordotonal organ, in which sound-induced antennal or tympanal vibrations are transmitted to ciliated sensory neurons and transduced to receptor potentials. However, the molecular identity of the transducing ion channels in chordotonal neurons, or in any auditory system, is still unknown. Drosophila that are mutant for NOMPC, a transient receptor potential (TRP) superfamily ion channel, lack receptor potentials and currents in tactile bristles but retain most of the antennal sound-evoked response, suggesting that a different channel is the primary transducer in chordotonal organs. Here we describe the Drosophila Nanchung (Nan) protein, an ion channel subunit similar to vanilloid-receptor-related (TRPV) channels of the TRP superfamily. Nan mediates hypo-osmotically activated calcium influx and cation currents in cultured cells. It is expressed in vivo exclusively in chordotonal neurons and is localized to their sensory cilia. Antennal sound-evoked potentials are completely absent in mutants lacking Nan, showing that it is an essential component of the chordotonal mechanotransducer.